Trading, investment, scientific and technological cooperation between the Republic of China and the Republic of Belarus in the context of implementation of the One Belt, One Road foreign economic strategy - Gavrilko, Galina N.; Dashkevich, Dariya A.; Peiyu, Qi (Journal of the Belarusian State University. Economics, 2019)
This article provides insight into the dynamics and commodity pattern of the Chinese-Belarusian bilateral trade, the current state and prospects for the investment, scientif ic and technological cooperation between the two countries for the purposes of implementation of the One Belt, One Road foreign economic strategy. With the advancement and f inancial support of the project, the Chinese-Russian bilateral balance of economic relations will be shifting in favour of China. Russia will act as a «subordinate partner»; its global economic and f inancial interests will be represented less than Chinese in the global economy.